Africa and its “Chinese” debt in the time of covid-19 - (:unkn) unknown (My University, 2021)
Given the health situation we face in 2020, the International Monetary Fund (IMF) and the World Bank, the G20, the Paris Club and even Pope Francis have spoken out in favour of debt relief for the most indebted countries, at the forefront of which are many African countries, China being more or less in the dock. Confronted with the media and political overbidding, we wonder in this article what is the real weight of African debt to China, what does this debt mean and what role China and its companies play? What influence does this debt have in the development strategy of African countries?
Keywords: African Research